Musculoskeletal Education: An Assessment of the Value of the American Academy of Pediatrics Musculoskeletal Boot Camp Course in Improving Clinical Confidence of Pediatricians Managing Common Musculoskeletal Conditions. (May 2021) - Crenshaw, Megan L.; Piazza, Brian R.; Otsuka, Norman Y.; Schwend, Richard M.; Alexander, Niccole; Hennrikus, William
In 2016, the American Academy of Pediatrics Section on Orthopaedics established an annual Musculoskeletal (MSK) Boot Camp course to fill the gaps in MSK knowledge, performance, and outcomes for pediatricians and primary care doctors. A standardized one-day curriculum of key MSK topics was developed including short lectures, hands-on workshops, debates, live webinars, and Q&A sessions. A survey was created to evaluate attendee confidence related to diagnosing 20 common MSK conditions in children and adolescents at the beginning and end of the course. Confidence in diagnosing the conditions was gauged using a 6-point Likert-type scale. A two-sample t test was used to compare overall confidence score pre- and post-seminar. In addition, each subtopic was analyzed. The average pre-seminar confidence score was 3.92 versus 4.86 post-seminar. All categories demonstrated a statistically increased confidence score post-seminar ( P < .0001). Live MSK continuing education for pediatricians is effective in improving confidence in clinical practice.